2008
DOI: 10.1111/j.1525-1438.2007.00965.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of recurrence rates and times with posttreatment human papillomavirus status in patients treated with loop electrosurgical excision procedure conization for cervical squamous intraepithelial lesions

Abstract: The aim of the present study was to assess recurrence rates and times in patients with squamous intraepithelial lesion (SIL) of the uterine cervix treated with loop electrosurgical excision procedure (LEEP) conization, in order to define categories of patients who have a different risk of recurrence and who need a different surveillance protocol. This study was carried out on 119 consecutive patients who underwent LEEP. All patients were followed up with cervical smear and colposcopy after 3, 6, and 12 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 30 publications
2
29
0
3
Order By: Relevance
“…most of the studies demonstrate that the margins affections increase the risk of illness residual [24,25] significantly. In the study of Houfflin-Debargue et al [26] the patients with positive margins were 36%, in the study of Serati et al [27], 32% of the patients presented margins affections and it was found that this was the factor more important predictor of recurrent illness, the same as in the works of Prato [28] and Baloglu et al [29].…”
Section: Design Methodologicalsupporting
confidence: 59%
“…most of the studies demonstrate that the margins affections increase the risk of illness residual [24,25] significantly. In the study of Houfflin-Debargue et al [26] the patients with positive margins were 36%, in the study of Serati et al [27], 32% of the patients presented margins affections and it was found that this was the factor more important predictor of recurrent illness, the same as in the works of Prato [28] and Baloglu et al [29].…”
Section: Design Methodologicalsupporting
confidence: 59%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The high sensitivity of the HPV test (typically 95-100%) means that a negative HPV test result is a highly certain indicator of effective treatment (ie. high negative predictive value).…”
Section: Introductionmentioning
confidence: 99%
“…Being aware of this we must use these tools in the best cost-effective protocol, which will be most accurate in diagnosis and sparing in treatment. Studies have shown a higher sensitivity in detection of residual/recurrent disease with the use of combined testing (cytology and HPV) [5,6]. Combined testing raises the cost of follow-up and in some countries like Croatia, with a tradition of high quality cytology this is unacceptable.…”
Section: Introductionmentioning
confidence: 99%